Analisis Media Pembelajaran Berbasis Power Point terhadap Motivasi Belajar pada Mata Pelajaran PAI di SD Negeri 16 Air Tawar Timur - Deni, Eka Putri; Alfurqan, Alfurqan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to analyze power point-based learning media as a learning medium used by teachers, in Q.S At-tin material. The approach used was through a qualitative method with a descriptive type. The data sources in this study were obtained from informants, namely teachers and students. Data collection techniques were obtained by means of observation, interviews and documentation. Data analysis techniques in this study used the Miles and Hubermen models with three techniques namely: data reduction, data presentation and conclusions. The results of this study are: (1), how is the use of power point-based learning media on learning motivation in PAI subjects in Class V. (2) what are the advantages and disadvantages of using power point media on learning motivation in PAI subjects in Class V. (3) how is the learning motivation from using power point-based learning media in class V. in research the need for learning media to support the learning process, so that students become interested and motivated, researchers can conclude that this power point media is suitable for use in learning and makes it easier for teachers to delivering material in class V Elementary School.